2016
DOI: 10.14419/ijbr.v4i2.6431
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of biogas production from animal wastes by anaerobic digestion

Abstract: This study compares biogas production from cattle dung, piggery faeces and poultry wastes under different environmental conditions by anaerobic digestion as a means of managing municipal solid wastes and was conducted in the Department of Biological Sciences, Benue State University, Makurdi from 1st August, 2011 to 13th December, 2011. A 6 Kg of each of waste was mixed with four litres of water and loaded into three locally constructed digesters. The biogas produced was measured using water displacement method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The biogas produced was measured using water displacement method for every 5 days. It was found that piggery faeces gave the highest yield of biogas (1.07 l kg -1 ), followed by cattle dung (0.71 l kg -1 ), with poultry wastes the least (0.42 l kg -1 ) all under direct sunlight (Soom et al, 2016). Microbial biomass in terms of dehydrogenase and cellulase activity was also determined at 15 days interval for eight weeks during batch digestion.…”
Section: Resultsmentioning
confidence: 99%
“…The biogas produced was measured using water displacement method for every 5 days. It was found that piggery faeces gave the highest yield of biogas (1.07 l kg -1 ), followed by cattle dung (0.71 l kg -1 ), with poultry wastes the least (0.42 l kg -1 ) all under direct sunlight (Soom et al, 2016). Microbial biomass in terms of dehydrogenase and cellulase activity was also determined at 15 days interval for eight weeks during batch digestion.…”
Section: Resultsmentioning
confidence: 99%